Pengaruh Persepsi Kemudahan terhadap Kepuasan Pengguna Kartu Debit pada Mahasiswa Ilmu Administrasi Negara - Ria Maylani Astuti; Sinta Westika Putri (Jurnal Ilmiah Dan Karya Mahasiswa, 2026)
This research is motivated by the decline in the use of national debit cards and low user satisfaction among students. The purpose of the study was to test the effect of convenience perception on debit card user satisfaction in State Administration students of Padang State University. This study used an associative quantitative approach with a population of 1,247 students and a sample of 93 respondents selected through a simple random sampling technique using the Slovin formula with an error rate of 10%. Data was collected through a Likert scale questionnaire that has been tested for validity and reliability. Data analysis includes descriptive analysis, classical assumption test, correlation coefficient, simple linear regression, determination coefficient, and t-test. The results showed that the perception of convenience was in the category of sufficient (75%) and user satisfaction was also sufficient (74.2%). The regression equation was obtained Y = 10.944 + 0.50X with a correlation coefficient R = 0.668 and a determination coefficient R² = 44.7%. The t-test produced a significant value (t = 8.571; p < 0.001), so it can be concluded that the perception of convenience has a positive and significant effect on the satisfaction of using a debit card. The implications of this study confirm the importance of strong digital governance to encourage sustainable innovation, maintain satisfaction, and maintain user loyalty in digital payment systems.